The Potential Role of Exosomes in the Treatment of Brain Tumors, Recent Updates and Advances - Huang, Zoufang; Keramat, Shayan; Izadirad, Mehrdad; Chen, Zhe-Sheng; Soukhtanloo, Mohammad (Frontiers in Oncology, 2022)
Exosomes are small endosomal derived membrane extracellular vesicles that contain cell-specific cargos such as lipid, protein, DNA, RNA, miRNA, long non-coding RNA, and some other cell components that are released into surrounding body fluids upon the fusion of multivesicular bodies (MVB) and the plasma membrane. Exosomes are a one-of-a-kind cell-to-cell communication mechanism that might pave the way for target therapy. The use of exosomes as a therapeutic potential in a variety of cancers has been and is still being investigated. One of the most important of these has been the use of exosomes in brain tumors therapy. Exosome contents play a crucial role in brain tumor progression by providing a favorable niche for tumor cell proliferation. Also, exosomes that are secreted from tumor cells, lead to the protection of tumor cells and their proliferation in the tumor environment by reducing the inflammatory response and suppression of the immune system. Although some treatment protocols such as surgery, chemotherapy, and radiotherapy are common in brain tumors, they do not result in complete remission in the treatment of some malignant and metastatic brain tumors. Identifying, targeting, and blocking exosomes involved in the progression of brain tumors could be a promising way to reduce brain tumor progression. On the other way, brain tumor therapy with effective therapeutic components such as siRNAs, mRNAs, proteins, could be developed. Finally, our research suggested that exosomes of nanoscale sizes might be a useful tool for crossing the blood-brain barrier and delivering effective content. However, further research is needed to fully comprehend the potential involvement of the exosome in brain tumor therapy protocols.